ANALISIS VEGETASI AGROEKOSISTEM DAN KERAGAMAN JENIS PISANG (Musa spp.) DI DESA MAJASARI KABUPATEN GARUT - M. Khais Prayoga dan Ade Ismail (Program Studi Agroteknologi Faperta UNIBBA, 2022)
Banana is a horticultural commodity that gets priority to be researched and developed because it has the potential to meet domestic or export needs. Majasari Village, Cibiuk District, Garut Regency, West Java Province is one of the centers of banana production with productivity reaching 27 tons/ha. So far there has been no study related to the analysis of agro-ecosystem vegetation and the diversity of banana species in Majasari Village so that the diversity of banana species is unknown and causes there is still much potential banana germplasm that has not been characterized. Therefore, it is necessary to analyze the level of diversity of banana species and their agroecosystem biodiversity in Majasari Village in supporting plant breeding activities. The study was conducted at 21 locations in Majasari Village where the determination of the location was carried out by purposive sampling. The method used in this study is a survey and exploration method as well as interviews with farmers. The results showed that Majasari Village had a high diversity of species in the banana agroecosystem, both annual crops (H = 2.53) and annual plants (H = 2.54). In the banana agroecosystem, 18 types of annual plants were found, 23 types of annual plants were found. The most dominating annual crop is cassava with an INP value of 53,966, while the most dominating annual plant is teak with an INP value of 48,790. From 21 banana agroecosystems in Majasari village, 20 types of bananas were found, consisting of 12 types of fruit bananas and 8 types of processed bananas with a high diversity index (H = 2.67). The dominant type of banana is Ambon banana with an INP value of 37.444%.